2010
DOI: 10.1158/0008-5472.can-10-0382
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Phosphorylated NPM1 to Sites of DNA Damage through RNF8-Dependent Ubiquitin Conjugates

Abstract: Protein accumulation at DNA double-strand breaks (DSB) is essential for genome stability; however, the mechanisms governing these events are not fully understood. Here, we report a new role for the nucleophosmin protein NPM1 in these mechanisms. Thr199-phosphorylated NPM1 (pT199-NPM1) is recruited to nuclear DNA damage foci induced by ionizing radiation (IR). Foci formation is impaired by depletion of the E3 ubiquitin ligases RNF8 and RNF168 or the E2 Ubc13, and pT199-NPM1 binds to Lys63-linked ubiquitin polym… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 46 publications
4
122
1
Order By: Relevance
“…4). In agreement with this view, many reports point to the involvement of NPM1 in different aspects of the DDR, yet, the exact contribution(s) of this protein to the stress response is currently elusive (31,79,127). It is worth pointing out that the lack of NPM1 has been proved to sensitize cells to genotoxins that elicit a BER response and that APE1 catalytic activity is impaired in NPM1 knock out cells (150).…”
Section: The Paradigmatic Example Of the Ape1/npm1 Interactionmentioning
confidence: 78%
“…4). In agreement with this view, many reports point to the involvement of NPM1 in different aspects of the DDR, yet, the exact contribution(s) of this protein to the stress response is currently elusive (31,79,127). It is worth pointing out that the lack of NPM1 has been proved to sensitize cells to genotoxins that elicit a BER response and that APE1 catalytic activity is impaired in NPM1 knock out cells (150).…”
Section: The Paradigmatic Example Of the Ape1/npm1 Interactionmentioning
confidence: 78%
“…Furthermore, a comparable radioresistant and radiosensitive tumor model of human NPC was established, and the level of these three proteins was compared in vivo. The results indicated that NPM1 (also known as nucleolar phosphoprotein B23) is a molecular chaperone involved in numerous cellular processes, including centrosome duplication, ribosome biogenesis, cell-cycle progression (12) and DNA damage repair (13). Enhanced NPM1 expression causes uncontrolled cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…A functional nuclear export signal and the capacity to bind to the Ran-Crm1 nuclear export signal-dependent nuclear export complex, are required to localize NPM to centrosomes and control their duplication . T199 phosphorylation has been also linked to specific NPM localization in nuclear speckles where it represses pre-mRNA processing (Tarapore et al, 2006) and, more recently, T199 phosphorylated NPM has been shown to accumulate at sites of DNA damage favoring DNA repair (Koike et al, 2010). T199 together with T219, T234 and T237 are phosphorylated before mitosis by the Cdk1-cyclinB complex, abolishing the RNA binding activity of NPM (Peter et al, 1990;Okuwaki et al, 2002).…”
Section: Regulation Of Npm Activities Through Post-translational Modimentioning
confidence: 99%